Analisis Faktor Penyebab Kemiskinan: Studi Kasus Nelayan Tradisional di Kelurahan Barombong Kecamatan Tamalate - Silalahi, Glory Mei Sanada; Maddatuang; Musyawarah, Rahma (Journal of Geographical Sciences and Education, 2024)
The problem of poverty is a tough homework assignment for the Indonesian government. The poverty rate is something that is always highlighted every year. This study aims to analyze the factors that cause poverty, the characteristics of poverty, and the programs used to reduce poverty in traditional fishing communities living in Barombong Village. This research uses descriptive methods and analyzes data both obtained directly (primary data) and existing data (secondary data). The results showed the following: Factors that cause poverty in traditional fishermen in Barombong Village include six aspects, namely the quality of human resources, alternative employment, limited business capital, technology used, institutional factors, and consumptive behavior of fishermen. The poverty experienced by traditional fishermen in Barombong Village can be described in the form of natural poverty and cultural poverty. Programs to overcome the poverty of fishermen in Barombong Village focused on meeting basic needs, access to basic services, and fishing equipment.